The role of digital well-being in supporting university students' learning and mental health - Samsudin, Norshuhada; Mohd Rosly, Wan Nur Shaziayani; Omar, Mawardi; Syed Abdullah, Sharifah Sarimah (Unit Penerbitan JSKM, 2025)
In the digital age, university students rely heavily on technology for learning, communication, and academic productivity. While digital tools offer numerous educational benefits, excessive and unmanaged usage can negatively impact students' mental health and academic performance. This paper explores the concept of digital well-being and its significance in fostering a balanced academic experience. It examines the psychological effects of digital overuse such as stress, anxiety, sleep disturbances, and digital burnout and discusses how mindful technology practices can enhance concentration, emotional resilience, and social interaction. Drawing on recent literature, the study also highlights practical strategies for promoting digital well-being, including screen time management, digital detox activities, and institutional support. The findings emphasize the importance of cultivating healthy digital habits to ensure that technology serves as a tool for learning rather than a source of distress. Ultimately, promoting digital well-being is essential for creating supportive university environments that nurture both academic success and student mental health.